2017
DOI: 10.1007/s11250-017-1411-8
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ breeding practices and traits of economic importance for indigenous chicken in RWANDA

Abstract: Data on breeding practices and traits of economic importance for the indigenous chicken (IC) were collected through personal interviews using structured questionnaires and direct observations of chicken management practices. The study was conducted from November 2015 to January 2016 in Rwamagana, Rulindo, Ruhango, Kicukiro and Muhanga districts of Rwanda. Data were collected and analysed through computation of indices, which represented a weighted average of all rankings of a specific trait. Spearman's non-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
4
17
1
1
Order By: Relevance
“…However, this genotype is renowned for its high adaptability to the prevailing hot-dry tropical environment of Nigeria (Yakubu and Ari 2018) and good scavenging ability. Some of the merits indicated by farmers for the choice of a BSC body size-cock, BSH body size-hen, SFC supplementary feed consumption-cock, SFH supplementary feed consumption-hen, ENH egg numberhen, EZH egg size-hen, SAC scavenging ability-cock, SAH scavenging ability-hen, MTC meat taste-cock, MTH meat taste-hen, ESC ease of salescock, ESH ease of sales-hen, SD standard deviation a The lower the mean, the more important the trait particular genotype in the current study are similar to the egg productivity, body size and fast growth traits reported by Sisay et al 2018and Mahoro et al (2018). Gender differences in the present study as regards the choice of Sasso chicken breed BSC body size-cock, BSH body size-hen, SFC supplementary feed consumption-cock, SFH supplementary feed consumption-hen, ENH egg number-hen, EZH egg size-hen, SAC scavenging ability-cock, SAH scavenging ability-hen, MTC meat taste-cock, MTH meat taste-hen, ESC ease of sales-cock, ESH ease of sales-hen a The lower the mean, the more important the trait may be attributed to poultry keeping objectives and varied importance attached to the chicken genotype by both male and female farmers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, this genotype is renowned for its high adaptability to the prevailing hot-dry tropical environment of Nigeria (Yakubu and Ari 2018) and good scavenging ability. Some of the merits indicated by farmers for the choice of a BSC body size-cock, BSH body size-hen, SFC supplementary feed consumption-cock, SFH supplementary feed consumption-hen, ENH egg numberhen, EZH egg size-hen, SAC scavenging ability-cock, SAH scavenging ability-hen, MTC meat taste-cock, MTH meat taste-hen, ESC ease of salescock, ESH ease of sales-hen, SD standard deviation a The lower the mean, the more important the trait particular genotype in the current study are similar to the egg productivity, body size and fast growth traits reported by Sisay et al 2018and Mahoro et al (2018). Gender differences in the present study as regards the choice of Sasso chicken breed BSC body size-cock, BSH body size-hen, SFC supplementary feed consumption-cock, SFH supplementary feed consumption-hen, ENH egg number-hen, EZH egg size-hen, SAC scavenging ability-cock, SAH scavenging ability-hen, MTC meat taste-cock, MTH meat taste-hen, ESC ease of sales-cock, ESH ease of sales-hen a The lower the mean, the more important the trait may be attributed to poultry keeping objectives and varied importance attached to the chicken genotype by both male and female farmers.…”
Section: Discussionsupporting
confidence: 82%
“…The observation on body size is in consonance with the findings of Muchadeyi et al (2009) where the trait was ranked first among the criteria for choosing chicken breeding stock. Similarly, Mahoro et al (2018) included body size and egg yield among the important economic traits to select the indigenous chickens. In a related study, Markos et al (2016) ranked egg number and body weight as first and second, respectively, while Asmelash et al (2018) reported that egg size was highly rated compared to other traits in village chicken.…”
Section: Discussionmentioning
confidence: 99%
“…However, these programmes have not been sustainable due to decreased broodiness in the hybridized birds, unpredictable stock, and the high cost of buying and sustaining exotic cocks for breeding purposes. Additionally, recent global efforts to preserve native genetic resources pose a threat to such programmes [4]. There is, therefore, a need for the development of an alternative strategy to genetic improvement and conservation of IC.…”
Section: Introductionmentioning
confidence: 99%
“…These programmes, however, are not sustainable because of unpredictable stock and the prohibitive cost of buying and sustaining exotic cocks for breeding purposes in addition to decreased broodiness in the hybridized birds. Additionally, recent global efforts to preserve native genetic resources pose a threat to such programmes, [3]. There is, therefore, the need for an alternative approach to genetic improvement and conservation of IC.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, genetic enhancements need a resolute breeding objective, sustainable breeding plans, and an in-depth comprehension of the genetic diversity of prevailing genotypes and ecotypes [4]. Therefore, elucidating the genetic characteristics of the prevailing IC stock will not only augment genetic enhancement but will also expedite their preservation [3]. However, there is a scarcity of data on the genetic diversity of IC in Rwanda.…”
Section: Introductionmentioning
confidence: 99%